2022
DOI: 10.1186/s10020-022-00435-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism in biofilm infection: lessons from cancer

Abstract: Background Biofilm is a community of bacteria embedded in an extracellular matrix, which can colonize different human cells and tissues and subvert the host immune reactions by preventing immune detection and polarizing the immune reactions towards an anti-inflammatory state, promoting the persistence of biofilm-embedded bacteria in the host. Main body of the manuscript It is now well established that the function of immune cells is ultimately medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 406 publications
(688 reference statements)
0
16
0
3
Order By: Relevance
“…When the cells are embedded inside a matrix forming a biofilm, they are more protected against antimicrobials and antibiotics because of a slower growth rate and a lower diffusion rate of the compounds [ 69 ]. Cells in biofilms may even influence the leukocyte function of the host immune system [ 70 ] and the metabolism of immune cells, thus affecting the development and activation of immune reactions [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the cells are embedded inside a matrix forming a biofilm, they are more protected against antimicrobials and antibiotics because of a slower growth rate and a lower diffusion rate of the compounds [ 69 ]. Cells in biofilms may even influence the leukocyte function of the host immune system [ 70 ] and the metabolism of immune cells, thus affecting the development and activation of immune reactions [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The LPS of H. pylori stimulates the release of IL-8, IL-6, IL-10, IL-12, and also induces the production of TNF-α and PGE2. H. pylori has several virulence factors that play a role in pathogenicity [ 26 ]. Factors including BABA, HOPP, adherence lipoprotein, HspA, HspB, disulfide reductase, purines, alcohol dehydrogenase, PPK, RO53, FLdA, and amma-glutamyl transpeptidase promote carcinogenesis by increasing pathogenicity of H. pylori [ 27 ].…”
Section: Mechanisms Of Pathogenic Factors In H Pylorimentioning
confidence: 99%
“…IBD is often accompanied by gut dysbiosis 125 . Compared to the general population, patients with UC have a sixfold increased risk of developing colorectal cancer (CRC) 126,127 . Several studies have revealed that the administration of probiotics has the potential to improve mucosal barrier function and restore intestinal microbiota by altering the profile of the luminal BA pool 128–130 .…”
Section: Recent Advances Based On Microbiome In Ibd Treatmentmentioning
confidence: 99%